2012
DOI: 10.1007/s12603-012-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of skeletal muscle mass to fat-free mass ratios among different ethnic groups

Abstract: Our results suggest that relative SMM is not lower in Asian populations compared with European populations after adjusted by age and BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…The SM index for the high MS is greater than that previously reported for young Caucasian men (8.8 kg/m 2 ; mean age 31.4 years) using similar analytic techniques. 26 Previous research has shown total SM index gradually decreases with age, and is 11% lower in Japanese men aged 50-59 years (7.66 kg/m 2 ) and 16% lower in Japanese men aged 60-69 years (7.24 kg/m 2 ) when compared to Japanese young men (8.57 kg/m 2 ) aged 20-29 years. 2 Therefore, our findings suggest that MS with higher swimming distances maintain a high SM index, even greater than that of active (but presumably non-swimming) young men.…”
Section: Discussionmentioning
confidence: 89%
“…The SM index for the high MS is greater than that previously reported for young Caucasian men (8.8 kg/m 2 ; mean age 31.4 years) using similar analytic techniques. 26 Previous research has shown total SM index gradually decreases with age, and is 11% lower in Japanese men aged 50-59 years (7.66 kg/m 2 ) and 16% lower in Japanese men aged 60-69 years (7.24 kg/m 2 ) when compared to Japanese young men (8.57 kg/m 2 ) aged 20-29 years. 2 Therefore, our findings suggest that MS with higher swimming distances maintain a high SM index, even greater than that of active (but presumably non-swimming) young men.…”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, too rare are such data shared by the authors of papers on cut-off points. It is worth pointing out that subjects of various races differ significantly as far as their heights, but also their body compositions, are concerned [ 33 35 ]. The highest level of skeletal muscle mass is characteristic of the Black race, with the Caucasian one in the middle and the Asian one with the lowest level [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported a SM index of Japanese men aged 20 to 30 years (8.6 [SD 0.9]kg/m 2 ) as the reference value for men (Abe et al 2012d). For women, we recalculated a mean and SD of young women aged 20-30 years (6.0 [SD 0.9]kg/m 2 ) as the reference value using a previously reported data set (Abe et al 2012a). Therefore, the reference values for severe sarcopenia (2 SD below the sex-specific means) in men and women were 6.8 and 4.2 kg/m 2 , respectively.…”
Section: Body Composition and Anthropometrymentioning
confidence: 99%